Designing and empirical realization of horn antennas and waveguides in a 60 GHz wireless system - Ayesha, Sk. Laila; Aman, Synthia; Akhter, Sumaiya (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.